Case report of a rare yeast Cyberlindnera fabianii fungemia in preterm twin neonates from North India: Diagnostic and therapeutic challenge (Indian Journal of Case Reports, 2020)
Cyberlindnera fabianii infection has rarely been described in humans and only a few cases of human infections by this organism have been reported to date. Here, we present a case of premature twin neonates who were outborn and admitted for extremely low birth weight, early-onset sepsis, and patent ductus arteriosus. They were put on continuous positive airway pressure for 6 days and prolonged antibiotic course. Blood culture was positive for Candida sp. Antifungal drug fluconazole was added to the treatment regime which includes piperacillin-tazobactam and amikacin. Isolates were initially unidentified by conventional identification methods and showed reduced susceptibility to azoles. MALDI-TOF-MS identified the isolates as C. fabianii. Soon the neonates went into shock and cardiopulmonary arrest despite high ventilator support and died during treatment due to respiratory failure. This case report highlights C. fabianii as a rare fungal pathogen and emphasizes the importance of molecular methods such as matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS) in its accurate identification.